An Analysis of the Economic Growth Convergence of North Sumatra - Siahaan, Jhon Boyke; Athoillah, Moh. (Journal of Development Economic and Social Studies, 2025)
North Sumatra has experienced significant economic growth, which has driven the growth of other economic indicators. However, economic growth across regions in North Sumatra Province remains unevenly distributed. This study focuses on the analysis of economic growth convergence in the regencies/cities of North Sumatra Province during the period 2018-2022. The concept of convergence refers to the tendency of poorer regions to catch up with richer regions. By using the neoclassical growth theory and incorporating variables that influence economic growth, this study aims to promote economic convergence through a panel data regression approach. The results show a decrease in disparity indicated by sigma convergence, but the lagging regions have not been able to catch up with the more advanced regions as indicated by beta convergence. The variables affecting economic growth are the Human Development Index (HDI) and the open unemployment rate, while the realization of the Regional Budget does not have a significant impact